Nursing care for a patient with chronic insufficiency prepared for kidney transplant - Reczkowska, Justyna; Sławiński, Mirosław (Journal of Education, Health and Sport, 2021)
Admission: The term chronic renal failure (CHF) has been used since the beginning of medicine. In Poland, as in the rest of the world, there is a continuous increase in society who suffer from CKD in the uremic phase. Transplantation is considered to be the most optimal method of treating chronic renal failure. It is considered to be the most effective because the transplanted organ can take over all the functions that a healthy organ performs in the donor human body. Aim of the study: The aim of the study was to provide holistic care to a patient with chronic renal failure who was being prepared for organ transplant. Materials and methods: The study uses the method of an individual case, used in qualitative research. Case report: The subject of the study is a 45-year-old man with chronic renal failure caused by poorly treated arterial hypertension. After performing basic blood tests, he was referred to the Department of Nephrology due to the diagnosis of renal failure. The diagnosis was confirmed at the ward. Despite compliance with the recommendations, glomerular filtration was systematically deteriorating. The patient was reported for a pre-kidney transplant. After the first kidney transplant, the organ was rejected. The patient started a course of hemodialysis. After a year, another transplant was successfully performed. Conclusions: Nursing care for a patient with chronic renal failure prepared for transplantation requires careful observation of the patient as well as skilful diagnosis and appropriate response to his problems.